Profile of Visual-Spatial Intelligence In Solving Geometric of 11th Grades Viewed From Gender Differences - Sigit Rimbatmojo; Tri Atmojo Kusmayadi; Riyadi Riyadi (Universitas Sebelas Maret, 2017)
Visual-spatial intelligence is one of the multiple bits of intelligence that important to solve a mathematics problem, especially in geometry. This present research investigates the profile of students’ visual-spatial intelligence. This research focuses on analysis and description of students’ visual-spatial intelligence level generally and its aspect when solving the geometric problem. Visual-spatial intelligence aspect, there is imagination, pattern seeking, problem-solving, and conceptualization. Qualitative research with case study strategy was used in this research. The subject in this research involved 12 students of 11th grades chosen with purposive sampling. Data in this research were students’ visual-spatial intelligence test result and task based interviews. They were asked to complete visual-spatial intelligence test before interview. The data was analyzed based on visual-spatial intelligence aspect of female and male students. The results of this research show that female students have better pattern seeking and conceptualization. Meanwhile, male students have better in imagination and problem-solving.